Memilih Media Efektif dan Produktif dalam Media Dakwah - Efendi, Erwan; Ferdiansyah, Dafid; Fuady, Sajdatul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Da'wah is an important process in spreading religious messages. In the current digital era full of challenges, preachers must utilize media in an effective and productive way. This research aims to analyze and identify the most appropriate and effective media for preaching amidst technological advances. Through a survey of several groups of preachers, this research seeks to determine the preferences, trends and influence of certain media on understanding and acceptance of preaching messages. The results of this research provide important insights regarding strategies for selecting effective da'wah media that can increase community involvement and understanding of religious values. Therefore, this article attempts to provide guidance for preachers so they can take the right approach in choosing effective and efficient preaching media.